Analysis of the thermal performance of the novel assembled Chinese solar greenhouse with a modular soil wall in winter of Yinchuan, China - Cao, Yanfei; Xu, Hongjun; Shi, Miao; Zhang, Xueyan; Zhang, Yahong; Zou, Zhirong (International Journal of Agricultural and Biological Engineering, 2022)
In order to improve the thermal insulation and storage performance of Chinese solar greenhouses in winter, a novel assembled Chinese solar greenhouse (ACSG) without energy supplement in cold climatic areas was designed to evaluate and compare its thermal performance with that of conventional Chinese solar greenhouse (CSG). The thermal properties of both greenhouses were tested in field on cold winter days in Ningxia, China. The results indicated that the land utilization rate of ACSG was 19.3% higher than that of CSG. On a typical sunny day (the lowest outdoor temperature was −22.0°C) and typical cloudy day (the lowest outdoor temperature was −19.7°C) during the experiment, the minimum indoor temperature of ACSG was respectively 1.7°C and 2.0°C higher than that of CSG. The results for 24 consecutive days (the average outdoor daily minimum air temperature was −19.0°C) showed that the average minimum indoor temperature of ACSG was 1.4°C higher than that of CSG (p<0.05). The modular soil wall attached with colored steel polystyrene boards would be exploited as the north wall of CSG in Yinchuan area.Keywords: thermal performance, solar greenhouse, north wall, composite wall structure, soil blockDOI: 10.25165/j.ijabe.20221505.6759Citation: Cao Y F, Xu H J, Shi M, Zhang X Y, Zhang Y H, Zou Z R. Analysis of the thermal performance of the novel assembled Chinese solar greenhouse with a modular soil wall in winter of Yinchuan, China. Int J Agric & Biol Eng, 2022; 15(5): 70–77.